2017
DOI: 10.1002/jcu.22517
|View full text |Cite
|
Sign up to set email alerts
|

Calcifying epithelioma of malherbe (Pilomatrixoma): Clinical and sonographic features

Abstract: PurposeThe purpose of this study was to describe the clinical and sonographic features of calcifying epitheliomas (pilomatrixomas).MethodsWe retrospectively reviewed the clinical data and sonographic appearances of 59 cases of calcifying epitheliomas in 58 patients that were confirmed pathologically.ResultsThe mean age of the patients was 26 years (range, 5–69 years) and the female‐to‐male ratio was 1.2. All masses were located in subcutaneous soft tissues. Overall, 76.3% of the cases were located in the head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 16 publications
(24 reference statements)
4
34
0
Order By: Relevance
“…Moreover, they are characteristically situated entirely in the subcutaneous fat layer, whereas TCs are located in subcutaneous soft tissues close to the dermis. The characteristic sonographic features of pilomatricoma also differ from TCs in that they are typically well‐defined solid calcified masses with moderate intrinsic vascularity and a peripheral hypoechoic rim corresponding to the connective tissue capsule . Most TCs are hypoechoic masses containing calcifications with posterior sound enhancement but no color Doppler signals …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they are characteristically situated entirely in the subcutaneous fat layer, whereas TCs are located in subcutaneous soft tissues close to the dermis. The characteristic sonographic features of pilomatricoma also differ from TCs in that they are typically well‐defined solid calcified masses with moderate intrinsic vascularity and a peripheral hypoechoic rim corresponding to the connective tissue capsule . Most TCs are hypoechoic masses containing calcifications with posterior sound enhancement but no color Doppler signals …”
Section: Discussionmentioning
confidence: 99%
“…Lin et al revealed predominant hypoechoic lesions on ultrasound images of pilomatrixoma. The tumor may show ossifications that can be detected in ultrasound (19). In the present case, the tumor was of dense internal hyperechoic signals and showed a distinct border.…”
Section: Discussionmentioning
confidence: 45%
“…Ultrasound examination is very suitable for the initial examination of this skin tumor (19). Lin et al revealed predominant hypoechoic lesions on ultrasound images of pilomatrixoma.…”
Section: Discussionmentioning
confidence: 99%
“…On color Doppler imaging, pilomatrixomas can show a variable degree of vascularity both in the periphery and internally. 15 In our SCM series, the hypervascularity only showed a perilesional pattern. 17 Interestingly, HS was identified as an associated lesion in 33% of cases (3 of 9).…”
Section: Discussionmentioning
confidence: 57%
“…This benign tumor appears on US imaging as a well-defined dermal and subcutaneous nodule. 15 Its most common form of presentation is the target type, with a hypoechoic rim and a hyperechoic center that contains a variable amount of hyperechoic spots that correspond to calcium deposits, which may show different intensities of a posterior acoustic shadowing artifact. 16 In SCM, no internal calcium deposits were observed in our cases or reported in the literature.…”
Section: Discussionmentioning
confidence: 99%